The relationship between physical activity and mental health: Is more always better? - Popov, Stanislava; Volarov, Marija; Rakočević, Nikolija (Primenjena psihologija, 2023)
The current study was designed to examine the relationship between physical activity and mental health. We investigated whether individuals who perceive themselves as physically inactive, recreationists, or active athletes differ in positive (positive affect, subjective well-being, unconditional self-acceptance) and negative mental health outcomes (depression, anxiety, stress, negative affect, conditional self-acceptance). Furthermore, we investigated whether the total level of leisure-time physical activity predicted different mental health indicators. Analysis revealed that physically active respondents (recreationists and active athletes) seem to have better overall mental health status than physically inactive ones. Precisely, physically inactive individuals scored higher on all measures of negative mental health indicators, and lower on all measures of positive mental health indicators, compared with the participants from the two other groups. At the same time, there were no significant differences in these measures between recreationists and active athletes. Besides, a positive association was found between the weekly frequency of leisure-time activity and only two positive indicators of mental health (positive affect and subjective well-being)of all tested. The obtained results suggest that it is often more relevant for mental health whether someone is physically active or not, in general, than how frequently they exercise.